MENTORING ELEMENTARY SCHOOL STUDENTS AND TEACHERS IN LEARNING TAJWEED AL-QUR'AN - Rohimah,; Siti Nuri Nurhaidah,; Asmawi, Moh (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2024)
In 2022, the As-Syafiiyah Islamic University in Jakarta's Islamic Education Program held a community service program in Singaraja Village, Indramayu District, West Java. The goal of this event is to: (1) encourage Islamic Elementary School (Madrasah Ibtidaiyah) teachers to implement a curriculum-based approach to teaching the Science of Qur'anic Recitation (The Science of Qur'anic Tajweed), (2) motivate elementary school teachers to make the Science of Qur'anic Recitation enjoyable and accessible, and (3) inspire students. The most common method is participatory delegation, in which citizens and leaders collaborate to provide public services. The conference will be held in September 2023, with 60 students, 7 lecturers, 37 Natural Resources (SDA) teachers from 9 schools, and 11 student classes participating. The findings of this study show that: 1) students benefited long-term from implementing a classroom learning strategy; 2) students felt helped in understanding the Science of Qur'anic Recitation (The Science of Qur'anic Tajweed), became more interactive in their learning, and believed that the Science of Qur'anic Recitation is not difficult; and 3) students believed that the Science of Qur'anic Recitation is not difficult. 3) The majority of Islamic Elementary School (MI) teachers in Singaraja Village, Indramayu District, do not yet understand the implementation of problem-based learning and project-based learning approaches; 4) The majority of MI teachers in Singaraja Village, Indramayu District, continue to struggle with composing Higher Order Thinking Skills (HOTS) questions; 5) Some teachers struggle with solving literacy-related questions; and 6) Positive responses were received from students.